Exploring the Isomer Dependent SERS Spectra of (diphenylphosphoryl)(pyridin-2, -3, and -4-yl)methanol Adsorbed on Gold Nanocolloids. (29th May 2014) - Pięta, Ewa; Proniewicz, Edyta; Boduszek, Bogdan; Olszewski, Tomasz K.; Kim, Younkyoo; Proniewicz, Leonard M.
Abstract : The surface-enhanced Raman scattering (SERS) spectra of three aminophosphonate derivatives of pyridine: (diphenylphosphoryl)(pyridin-2-yl)methanol (α -Pyr), (diphenylphosphoryl)(pyridin-3-yl)methanol (β -Pyr), and (diphenylphosphoryl)(pyridin-4-yl)methanol (γ -Pyr) were measured after immobilization onto colloidal gold surface. Changes in the wavenumber, broadness, and enhancement between the corresponding Raman and SERS bands allowed to deduce orientation of the α -, β -, and γ -isomers (α -, β -, and γ -refer to the position of the substituent relative to the ring nitrogen atom) of aminophosphonate derivatives of pyridine on the gold surface. Briefly, it was demonstrated that the α -Pyr and β -Pyr show the same mode of adsorption, whereas the adsorption process of the γ -Pyr isomer differs in this regard that pyridine assists in the interaction with the gold surface.